TINJAUAN POTENSI WISATA PADA PANTAI HUNIMUA, DESA LIANG, KECAMATAN SALAHUTU, KABUPATEN MALUKU TENGAH - Anthoneta T Waelauruw (Jurnal Administrasi Terapan, 2023)
The analytical method in the form of a theoretical study of SWOT Analysis combines 4 factors or compositions precisely on how to prepare strengths, overcome weaknesses, find opportunities and strategies to face various threats. The expected result is that the potential that exists at Hunimua Beach is developed into a beach tourism that has strengths, can overcome existing weaknesses, finds opportunities for Hunimua Beach, and has a strategy to face threats that come both from internal as well as external.The conclusion of this writing is that there is a need to develop tourism potential through the provision of weak facilities such as: Toilets, parking lots, clean water, rest areas, bathrooms, rubbish bins and changing rooms. Management of tourist locations such as: arranging tourist locations to provide parking spaces, places to rest, renovating rooms or buildings that have been damaged to become supporting facilities and infrastructure in tourist locations, utilizing shady trees to become tree houses, Hemok hanging places for visitors. / tourists who come. Good institutional management by the Management in managing the Hunimua Beach tourist attraction (Tourism Service) by taking into account strengths such as: the area of the location, beautiful beaches and long white sand, having the highest local revenue of the 2 tourist attractions managed by the Tourism Office. Opportunities such as: the interest of the Regional Government and the Community in developing Hunimua Beach, are able to obtain even higher income.threats such as: Earthquake-prone locations, freedom of land rights.Keywords: Potential, Beach Tourism Objects, SWOT.